1994
DOI: 10.1002/depr.3050020602
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine in tricyclic refractory depression in adolescents

Abstract: In an open cross‐over trial, six hospitalized adolescents (15–18 years) with a DSM‐III‐R diagnosis of major depression, who had failed to respond to a trial of tricyclic antidepressant (TCA) with or without lithium augmentation, were treated with fluoxetine. Fluoxetine treatment (20–60 mg/day) was associated with a reduction in depression severity after 4 weeks, as measured by Hamilton Rating Scale for Depression. The Hamilton Rating Scale for Depression scores (HRSD) reduced significantly after 4 weeks, from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Controlled and uncontrolled studies have generally shown that tricyclic antidepressants (TCAs) are not more effective than placebo in the treatment of childhood and adolescent depression (Kramer and Feiguine 1981, Strober et al 1990, Boulos et al 1991, Geller et al 1990). The possible effectiveness of selective serotonin uptake inhibitors (SSRIs) is suggested in open trials (Boulos et al 1992, Jain et al 1992, Ghaziuddin et al 1995. The only published data on a double-blind placebo-controlled study of fluoxetine showed a moderate improvement (not reaching clinical significance) among 40 adolescents (aged 13-18 years) both at 8 weeks and at 24-month follow-up (Simeon et al 1990).…”
mentioning
confidence: 97%
“…Controlled and uncontrolled studies have generally shown that tricyclic antidepressants (TCAs) are not more effective than placebo in the treatment of childhood and adolescent depression (Kramer and Feiguine 1981, Strober et al 1990, Boulos et al 1991, Geller et al 1990). The possible effectiveness of selective serotonin uptake inhibitors (SSRIs) is suggested in open trials (Boulos et al 1992, Jain et al 1992, Ghaziuddin et al 1995. The only published data on a double-blind placebo-controlled study of fluoxetine showed a moderate improvement (not reaching clinical significance) among 40 adolescents (aged 13-18 years) both at 8 weeks and at 24-month follow-up (Simeon et al 1990).…”
mentioning
confidence: 97%
“…However, more recently attention has turned to the SSRIs, with their better side effect profile, and the fact that the noradrenergic system may not be fully developed until early adulthood, which may explain, in part, the differential response in adults and children (Goldman-Rakic & Brown, 1982). Open studies of SSRIs have shown them to be well tolerated and effective (Boulos et al, 1992 ;Ghaziuddin, Naylor, & King 1995 ;Waslick et al, 1999), in addition to a randomised controlled double blind trial (Emslie et al, 1997). A large (N l 432) multicentre, randomised clinical trial comparing the effectiveness of Fluoxetine, CBT, combination therapy and placebo is currently underway (Treatment for Adolescents with Depression Study, NIMH).…”
Section: Discussionmentioning
confidence: 97%
“…[137][138][139][140][141] For this reason, it has been the most extensively studied SSRI in the depressed young (table IV). There are 5 reports that did not employ a placebocontrolled design, [142][143][144][145][146] and also 2 double-blind studies that compared the antidepressant effects of fluoxetine with placebo. [147,148] In 1 of these studies fluoxetine was found to be superior to placebo.…”
Section: Fluoxetinementioning
confidence: 97%
“…[147] Effectiveness As can be seen in table IV, all 5 nonblind reports with fluoxetine described clinically significant reductions in symptomatology for most patients. [142][143][144][145][146] The first double-blind study comparing fluoxetine to placebo in depressed adolescents failed to show a significant drug effect. [147] However, the small sample size and/or a high rate of placebo response may account for this finding.…”
Section: Fluoxetinementioning
confidence: 98%
See 1 more Smart Citation